Risks of climate change effects on renewable energy resources and the effects of their utilisation on the environment - Girgibo, Nebiyu; Hiltunen, Erkki; Lu, Xiaoshu; Mäkiranta, Anne; Tuomi, Ville (Elsevier, 2024)
Renewable energy resources are essential for combating climate change. However, their use, production and collection have environmental impacts and climate change effects also affect them. The unique contributions were that the risks of climate change to renewable energy resources were addressed, which is addressed rarely before. Climate change, marked the increase of Greenhouse gases (GHGs), affects ground heat source, Asphalt/concrete-covered areas and borehole energy at about 0.5 risk levels. Toxicity emerges as the primary environmental impact from ground heat sources (0.7), asphalt/concrete-covered areas (0.6), borehole energy (0.9), and sediment heat energy production (1.6). Bioenergy sufficiency and cost affect bio-oil (2.25), biodiesel (1.9), bioethanol (2.4), biogas (2.3), forest biomass (2.3), and algae (2.3) at varying risk estimate levels. The most prevalent impact, observed across all bioenergy and biomass energy sources, is on biodiversity. Extreme weather phenomena impact ground wind energy (2.7), offshore wind energy (3.4), solar panels and collectors (1.3), and hydropower (1.2) at varying risk estimate levels. Ground and offshore wind energy have effects on birds and other animals at levels of about 1.3 and 1.1, respectively. Field-based biomass energy is affected by climate change more than other renewable energy resources. Ground heat sources were the least-affected type of renewable energy and the type with the fewest effects on the environment was solar energy/collectors. The significance of the study is that it helped to make it clear that renewables are safe for the environment. This study assists renewable energy sustainability by creating attractiveness and awareness of its risk-free facts to society. One of the novelties of the study is that new renewable energy sources were included – sediment heat, asphalt heat and water heat exchangers. The research concludes that even if the risks of renewable energy are much lower than fossil fuels, they are still significant and cannot be ignored.
Keywords: Renewable energy; Impacts on the environment; Climate change effects; Geothermal energy; Solar-based energy; bioenergy; fi=Energiatekniikka|en=Energy Technology|; fi=Tuotantotalous|en=Industrial Management|